2002
DOI: 10.1523/jneurosci.22-18-07862.2002
|View full text |Cite
|
Sign up to set email alerts
|

Caspase Cleavage of Mutant Huntingtin Precedes Neurodegeneration in Huntington's Disease

Abstract: Huntington's disease (HD) results from polyglutamine expansion in huntingtin (htt), a protein with several consensus caspase cleavage sites. Despite the identification of htt fragments in the brain, it has not been shown conclusively that htt is cleaved by caspases in vivo. Furthermore, no study has addressed when htt cleavage occurs with respect to the onset of neurodegeneration. Using antibodies that detect only caspase-cleaved htt, we demonstrate that htt is cleaved in vivo specifically at the caspase conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
246
1
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 352 publications
(261 citation statements)
references
References 48 publications
13
246
1
1
Order By: Relevance
“…Our results demonstrate that Htt is cleaved by caspase-2 only at the 552 site when probed with antibodies that detect caspasecleaved Htt fragments (neospecific antibodies to cleavage sites at 513 and 552) (Figure 1d). 31 These results indicate that, in vitro, caspase-2 cleaves Htt at amino acid 552 and correlates with our recent results demonstrating that Htt is also cleaved in vivo at the D552 caspase consensus site in pyramidal cortical neurons of YAC72 mice and HD brains. 31 However, these results do not necessarily explain how this cleavage event is initiated in vivo.…”
Section: Hd Is Specifically Cleaved By Caspase-2 At Caspase Consensussupporting
confidence: 90%
See 3 more Smart Citations
“…Our results demonstrate that Htt is cleaved by caspase-2 only at the 552 site when probed with antibodies that detect caspasecleaved Htt fragments (neospecific antibodies to cleavage sites at 513 and 552) (Figure 1d). 31 These results indicate that, in vitro, caspase-2 cleaves Htt at amino acid 552 and correlates with our recent results demonstrating that Htt is also cleaved in vivo at the D552 caspase consensus site in pyramidal cortical neurons of YAC72 mice and HD brains. 31 However, these results do not necessarily explain how this cleavage event is initiated in vivo.…”
Section: Hd Is Specifically Cleaved By Caspase-2 At Caspase Consensussupporting
confidence: 90%
“…BDNF levels are directed regulated by wild-type Htt and are reduced in HD transgenic mice and HD patient brains. 33 We find that caspase-2 cleaves Htt selectively at amino acid 552, which is the Htt caspase cleavage product detected in vivo both in early-grade HD postmortem tissue and in YAC transgenic mice expression mutant Htt, 31 and further that Htt directly interacts with specific caspases to form a cell-death complex. We found that caspase-2, -6, and -7 recruit Htt in an apoptosome-like complex.…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…10 The decreased apoptosis observed in the brain suggested a critical role for caspase 3 in the development of the central nervous system. Caspase 3 has also been implicated in cell death following a number of neurodegenerative insults including global ischaemia, 12,13 focal ischaemia, [14][15][16][17][18][19] transient ischaemia of the spinal cord, 20 neonatal cerebral hypoxia-ischaemia, [21][22][23] traumatic brain injury, [24][25][26] Alzheimer's disease, [27][28][29] Huntington's disease, [30][31][32] and Parkinson's disease. [33][34][35][36][37] It was therefore hypothesized that overexpression of caspase 3 may sensitize the animal to normal (physiological) apoptotic processes that occur during development and natural ageing and confer particular susceptibility to neurodegenerative insults.…”
Section: Introductionmentioning
confidence: 99%